2017
DOI: 10.1111/jace.14865
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanisms of lithium garnet pellets in ambient air: The effect of humidity and CO2

Abstract: Li 7 La 3 Zr 2 O 12 (LLZO) has been reported to react in humid air to form Li 2 CO 3 on the surface, which decreases ionic conductivity. To study the reaction mechanism, 0.5-mol Ta-doped LLZO (0.5Ta-LLZO) pellets are exposed in dry (humiditỹ 5%) and humid air (humidity~80%) for 6 weeks, respectively. After exposure in humid air, the formation of Li 2 CO 3 on the pellet surface is confirmed experimentally and the room-temperature ionic conductivity is found to drop from 6.45910 À4 S cm À1 to 3.61910 À4 S cm À1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
169
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(177 citation statements)
references
References 45 publications
8
169
0
Order By: Relevance
“…Carbon could be clearly detected by analysing the negatively charged secondary ions. It is assumed that carbon originates from CO 2 / Li 2 CO 3 [8]. (Note: Carbon in such concentration does not originate from a contamination during processing or handling (like for example oil contamination from high vacuum pumping systems): the intensity of carbon measured by SIMS in samples prepared with the same PVD system and handled and analysed in the same SIMS system were orders of magnitude smaller than the intensity shown in figure 2 [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbon could be clearly detected by analysing the negatively charged secondary ions. It is assumed that carbon originates from CO 2 / Li 2 CO 3 [8]. (Note: Carbon in such concentration does not originate from a contamination during processing or handling (like for example oil contamination from high vacuum pumping systems): the intensity of carbon measured by SIMS in samples prepared with the same PVD system and handled and analysed in the same SIMS system were orders of magnitude smaller than the intensity shown in figure 2 [14].…”
Section: Resultsmentioning
confidence: 99%
“…C. Ma et al [5] observed a Li + /H + exchange reaction on a time scale of seconds by monitoring the pH value of an aqueous suspension of garnet Li 7 La 3 Zr 2 O 12 , and found a Li + /H + exchange as high as ~ 64 % in de-ionized water. W. Xia et al [8] reported that a certain level of humidity appeared to be required for the reaction of lithium hydroxide (LiOH) and CO 2 to lithium carbonate (Li 2 CO 3 ). Dense pellets were exposed to rather dry (5 % relative humidity) as well as to humid (80 % relative humidity) air for six weeks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…of −1.53 eV. However, Li-H exchange mechanism provides the opportunity to consume more Li and form more Li 2 [29,31] In conclusion, the Li atom migration from Li metal to garnet as well as Li ion migration within Li-rich phase beneath the inner interphase were simulated by CI-NEB and AIMD calculations. of −0.01 eV, the direct decomposition of Li 7 La 3 Zr 2 O 12 into 0.5Li 2 O+1.5La 2 O 3 +Li 6 Zr 2 O 7 is more thermodynamically preferable.…”
mentioning
confidence: 87%
“…Firstly, the Li-rich interphase was formed through Li migration from Li metal into garnet inner surface and from deeper garnet bulk to inner surface, the above Li-rich interphase and the Li wettability to garnet has been confirmed experimentally and theoretically. [25][26][27] Different Li 2 CO 3 formation mechanisms have been recently investigated and proposed, including direct reaction with products of ZrO 2 and La 2 O 3 , [28] reaction mediated by preliminary Li-H exchange, [29][30][31] or reaction mediated by defects as Li/O vacancies. These above two steps concurrently determine the theoretical overall ASR, which was calculated as the magnitude order of which was calculated as 10 −2 ·cm 2 under ideal conditions.…”
mentioning
confidence: 99%